Value chain and stakeholder‐driven product platform design. Issue 3 (29th November 2019) - Choi, Sung Chun; Suh, Eun Suk; Park, Chan Jung
Abstract: Product platform design and development is an arduous process that involves multiple stakeholders both inside and outside of a company. However, owing to its benefits, product platform has been widely implemented in the industry. Although numerous methodologies for product platform option generation, selection, and optimization have been proposed and demonstrated through various case studies, only a few researchers have explored and demonstrated a product platform design process that considered various value chain impacts. Herein, a value chain and stakeholder‐driven product platform design process is introduced. The process is demonstrated through a case study, where different water purifier product platform options were generated and evaluated for their effects on value chain, such as organization structure, production line configuration, economic effect, and preferences of different stakeholders.